CIRCULAR ECONOMY – THE FUTURE OF SUSTAINABLE DEVELOPMENT - CHURIKANOVA, Olena; DENYSENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The work is devoted to the analysis of the main principles and approaches to the introduction of the circular economy concept at the state level. The article contains both the theoretical foundations of the introduction of the circular economy, the conceptual apparatus and the analysis of practical cases of the successful introduction of the principles in the global space. In addition, the main problems that may stand in the way of the successful implementation of the circular economy at the state level are outlined. The paper considers the main aspects of the introduction of the concept of circular economy at the state and regional levels. The conceptual apparatus of the circular economy is presented and illustrated, the differences and advantages in comparison with the generally accepted system of the linear economy are noted. Also, the structure of the circular economy at the micro, macro, and meso levels is considered in detail in the work, the key aspects of implementation in the spheres of production, consumption, waste management, and development support are noted. Considerable attention was paid in the study to the tools for the introduction of the circular economy both at the state and regional levels and at the level of other subjects of economic activity. The circular economy toolkit proposed for analysis was considered both in terms of the economic effect of its introduction, and from the point of view of the presence of a certain number of problems for each of the tools. The identified problems on the way to successful application of circular economy tools outlined the vector of further research in this direction with the aim of accelerating the transformation processes of the transition from a linear to a circular form of economy.
Keywords: circular economy; green economy; linear economy; circular economy implementation levels; circular economy tools